Implementasi Model Pembelajaran TGT dan Media Quizizz untuk Meningkatkan Hasil Belajar Matematika pada Siswa Kelas 3 di SDN 23 Ampenan - Yunita, Reta; Rokhmat, Joni; Triapuri, A. Hegar (YASIN, 2023)
This research is entitled: "Implementation of the TGT Learning Model and Quizizz Media to Improve Mathematics Learning Outcomes for Grade 3 Students at SDN 23 Ampenan". The aim of this research is to improve learning outcomes in mathematics lessons regarding angles through the Teams Games Tournaments type learning model for students in Class III SDN 23 Ampenan. The method used in this research is Action Research which consists of 2 (two) cycles, and each cycle consists of: Planning, Implementation, Observation and reflection. Based on the results of action research, the Teams Games Tournaments Type Learning Model can improve the Mathematics Learning Outcomes of Class III students at SDN 23 Ampenan. Furthermore, the researcher recommends: (1) Teachers who experience the same difficulties can apply the Teams Games Tournaments Type Learning Model to improve the Mathematics Learning Outcomes of Class III students. (2) In order to get maximum results, teachers are expected to better understand the Teams Games Tournaments Learning Model.